2005
DOI: 10.1038/sj.onc.1208646
|View full text |Cite
|
Sign up to set email alerts
|

Significance of HDAC6 regulation via estrogen signaling for cell motility and prognosis in estrogen receptor-positive breast cancer

Abstract: Histone deacetylase (HDAC) 6 is a subtype of the HDAC family; it deacetylates a-tubulin and increases cell motility. Here, we investigate the impact of an alteration of HDAC6 expression in estrogen receptor a (ER)-positive breast cancer MCF-7 cells, as we identified that HDAC6 is a novel estrogen-regulated gene. MCF-7 treated with estradiol showed increased expression of HDAC6 mRNA and protein and a four-fold increase in cell motility in a migration assay. Cell motility was increased to the same degree by stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
184
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(196 citation statements)
references
References 23 publications
9
184
1
2
Order By: Relevance
“…HDAC6 expression is induced by estradiol in MCF7 and other breast cancer cells, and its level of expression correlates with a better prognosis and response to endocrine therapy (19 -21). In addition, patients with ER-positive breast tumors who received tamoxifen as adjuvant therapy for two years have a better prognosis and survival rate when tumors expressed HDAC6 (19). Moreover, inhibition of HDAC6 enhanced heat shock protein 90-mediated maturation of matrix metalloproteinase-2, which was associated with increased breast cancer cell invasion in an in vitro model (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC6 expression is induced by estradiol in MCF7 and other breast cancer cells, and its level of expression correlates with a better prognosis and response to endocrine therapy (19 -21). In addition, patients with ER-positive breast tumors who received tamoxifen as adjuvant therapy for two years have a better prognosis and survival rate when tumors expressed HDAC6 (19). Moreover, inhibition of HDAC6 enhanced heat shock protein 90-mediated maturation of matrix metalloproteinase-2, which was associated with increased breast cancer cell invasion in an in vitro model (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, a portion of HDAC6 can be nuclear in some cells. Notably, experiments performed in breast cancer cells have revealed that HDAC6 is an estrogen target gene (19) and that HDAC6 protein is present in the nuclei of normal breast epithelial cells but is cytoplasmic in adjacent malignant cells (20,21). Moreover, these studies found that HDAC6 expression levels correlate with better prognosis and response to endocrine therapy in breast cancer (19 -21).…”
mentioning
confidence: 99%
“…Depending on the type of cancer, the HDAC6 expression level could be considered either as a good prognosis indicator (Zhang et al, 2004) or, in contrast, as a predictor of poor prognosis and tumor aggressiveness (Osada et al, 2004;Hayashi and Yamaguchi, 2006;Sakuma et al, 2006). Indeed, HDAC6 detection has been reported to correlate with survival in a subset of tamoxifen-treated ER-positive breast cancer patients (Saji et al, 2005). Another report identified positive HDAC6 staining with decreased survival in ER-positive breast cancer patients, using HDAC6 as a prototypical estrogen-regulated gene (Yoshida et al, 2004).…”
Section: Hdac6: a Therapeutic Target?mentioning
confidence: 99%
“…Multiple HDAC enzymes have been identified, of which HDAC1 to HDAC10 are expressed in malignant cells (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). To understand the spectrum of HDACs inhibited by droxinostat and determine whether selective HDAC inhibition is sufficient to sensitize cells to FAS and TRAIL, we examined the spectrum of HDAC enzymes inhibited by droxinostat.…”
Section: Droxinostat Selectively Inhibits Hdac3 Hdac6 and Hdac8mentioning
confidence: 99%